2005
DOI: 10.1158/1078-0432.ccr-04-0155
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of MetXia-P450 Gene Therapy and Oral Cyclophosphamide for Patients with Advanced Breast Cancer or Melanoma

Abstract: Purpose: MetXia-P450 is a novel recombinant retroviral vector that encodes the human cytochrome P450 type 2B6 gene (CYP2B6), Escherichia coli lacZ , and neomycin resistance marker genes. Cytochrome P450 enzymes are primarily expressed in the liver and convert the prodrug cyclophosphamide to an active phosphoramide mustard and acrolein. Gene-based delivery of CYP2B6 to the tumor site leads to local prodrug activation and higher concentrations of the active metabolites at the target site.Experimental Design: Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 17 publications
1
65
0
Order By: Relevance
“…Our findings demonstrate that despite an increase in chemosensitivity, tumor cell expression of the high K m CPA 4-hydroxylase enzymes P450 2B6 and P450 2B1, used in recent clinical trials, 20,21 does not lead to a measurable increase in i.t. 4-OH-CPA levels.…”
Section: Introductionmentioning
confidence: 61%
“…Our findings demonstrate that despite an increase in chemosensitivity, tumor cell expression of the high K m CPA 4-hydroxylase enzymes P450 2B6 and P450 2B1, used in recent clinical trials, 20,21 does not lead to a measurable increase in i.t. 4-OH-CPA levels.…”
Section: Introductionmentioning
confidence: 61%
“…P450 gene transfer can be achieved both in cell culture and in human xenograft models by using tumor cell replication-conditional herpesvirus (24,25) or adenovirus vectors (26) to effect efficient, tumor-selective P450 gene delivery. Recent phase I/II clinical trials support the clinical development of P450 GDEPT based on studies using cellular vectors to deliver P450 2B1 to advanced pancreatic cancer patients treated with ifosfamide (27,28) and retroviral vectors to deliver P450 2B6 to advanced breast cancer and melanoma patients given oral cyclophosphamide (29).…”
Section: Introductionmentioning
confidence: 99%
“…However, results of clinical trials have shown that, among other challenges, poor in vivo gene transfer efficiency poses a major obstacle for those approaches that rely on in vivo gene transfer into tumor cells. [1][2][3][4][5][6][7][8] This applies to 'suicide gene' therapy, oncogene antagonism, antiangiogenesis gene therapy and some forms of immunotherapy. Thus, intense efforts are being directed at modifying vectors and delivery systems in order to improve gene transfer.…”
Section: Introductionmentioning
confidence: 99%